2019
DOI: 10.15575/ijhar.v1i1.4109
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Characteristic of Halal Gelatin Extracted from Buffalo Hide with Addition of Pineapple Rind at Different Ratio

Abstract: The production of halal gelatin from buffalo hide waste which is animal be slaughtered according to Islamic law and using pineapple rind as an extraction agent was an alternative to produce halal gelatin. The availability of buffalo hide in Riau Province was stable and its hide had high protein content. This research was conducted to produced and determine the characteristics of halal gelatin from buffalo hide using solution of pineapple skin in terms of their physical and chemical properties. The Completely R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…In another study, Aprizal et al. (2019) produced halal gelatin from buffalo hides using pineapple rinds containing bromelain enzyme and found that the physicochemical characteristics such as (viscosity, color profile, pH value, moisture, and ash content) of the produced gelatin met the criteria from GMIA (2019). Moreover, Ahmad et al.…”
Section: Extraction Methods Of Gelatinmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study, Aprizal et al. (2019) produced halal gelatin from buffalo hides using pineapple rinds containing bromelain enzyme and found that the physicochemical characteristics such as (viscosity, color profile, pH value, moisture, and ash content) of the produced gelatin met the criteria from GMIA (2019). Moreover, Ahmad et al.…”
Section: Extraction Methods Of Gelatinmentioning
confidence: 99%
“…Arsyanti et al (2018) has reported on different alkaline pretreatment on the yield and properties of buffalo hide gelatin. A work on addition of pineapple rind at different ratio on buffalo hide for gelatin extraction has been reported by Aprizal et al (2019). It was revealed that different treatment settings can create gelatin of diverse quality; some had high gel strength, while others had low gel strength, and certain conditions can produce a decent yield of gelatin while others did not.…”
Section: Bovidae-based Gelatinmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of halal industry in the world has also spread to several countries in Southeast Asia, including Indonesia (Tieman, 2019;Wingett & Turnbull, 2020). At least the variants of goods and services that have become the object of discussion at the international business level are food and beverages, halal tourism (Aprizal, Mirdhayati, & Yendraliza, 2019), Muslim fashion and halal fashion (Ishak et al, 2016), halal media and recreation, Islamic banking (Oseni, Ali, & de Anca, 2019), Islamic microfinance (Alam, Gupta, & Shanmugam, 2017), halal pharmaceuticals (Kulsum, Adawiyah, Shofwaturrohmani, & Nurjanah, 2019), the handling of halal certification (Muhamed et al, 2019) and cosmetics (Swidi et al, 2010), as well as renewable energy (Chitrakorn, 2015).…”
Section: Introductionmentioning
confidence: 99%